O znaczeniu kodeksu cywilnego dla prawa międzynarodowego: [On the relevance of the Civil Code in relation to international law] (Studia Prawnicze / The Legal Studies, 2023)
Autor artykułu przedstawia wpływ regulacji nowego kodeksu cywilnego PRL na międzynarodowe stosunki osobiste i majątkowe w zakresie prawa cywilnego. Podkreśla doniosłą rolę nowych przepisów, które określają ramy prawne dla międzynarodowego obrotu handlowego. W swojej pracy przedstawia kwestie dotyczące treści wzajemnego stosunku systemu prawa cywilnego i międzynarodowego oraz znaczenie prawa wewnętrznego w kształtowaniu norm regulujących stosunki między państwami. Autor przedstawia wpływ kodyfikacji cywilistycznych na teorie i praktykę prawa międzynarodowego, szczególnie w kontekście rozwoju integracji gospodarczej pomiędzy państwami. The author of this article presents the impact of the regulations of the new Civil Code of the People's Republic of Poland on international personal and property civil law relations. He emphasises the momentous role of the new rules, which set the legal framework for international trade. His work presents issues concerning the content of the interplay between the civil and international law systems and the importance of domestic law in shaping the norms governing relations between states. The author outlines the impact of civil codifications on the theories and practice of international law, particularly in the context of the development of economic integration between states.